147 Risk of Development of New Onset Postoperative Cervical Deformity in Thoracolumbar Adult Spinal Deformity and Effect on Clinical Outcomes at 2-year Follow-up. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Soroceanu, Alex; Passias, Peter G.; Boniello, Anthony; Scheer, Justin K.; Schwab, Frank; Shaffrey, Christopher I.; Kim, Han Jo; Protopsaltis, Themistocles; Mundis, Gregory; Gupta, Munish; Klineberg, Eric; Lafage, Virginie; et al.
Abstract: INTRODUCTION: A high prevalence of residual cervical deformity (CD) has been identified following surgical treatment of adult spinal deformity (ASD). Development of new onset CD is less understood and its clinical impact unclear. This study quantifies the incidence of CD after ASD surgery, identifies predictors of development, and determines the impact outcomes. METHODS: Retrospective review of a prospective multicenter database yielded 215 patients with complete 2-year follow-up and full length x-rays including the cervical spine. CD was defined by: T1S-CL >20°, C2C7 SVA >40 mm, or C2C7 kyphosis >10°. Univariate analysis was performed using t -tests or tests of proportion. Multivariate logistic regression was used to determine independent predictors of new CD. The impact of CD on Health Related Quality of Life (HRQL) and satisfaction was measured using repeated measures mixed models or logistic regression as appropriate, accounting for potential confounders. RESULTS: Eighty-eight of 215 ASD patients did not have CD at baseline and 42 (47.7%) developed CD at 2 years postop. Univariate analysis revealed that patients who developed new cervical deformity in the post op period had a higher incidence of diabetes (14.29% vs 2.17%, P = .036) increased pre-op C2C7 SVA ( P = .04) and C2 slope ( P = .038) and smaller diameter rods used at surgery ( P = .0328). Independent predictors of new CD at 2 years included: diabetes (OR 10.49, P = .046) and increased preop TS-CL (OR 1.08/deg, P = .027). Ending instrumentation below T4 was a negative predictor of CD (OR 0.31, P = .019). Patients with and without CD experienced improvements in 2-year SF-36 ( P = .0001), Oswestry Disability Index ( P = .0001) and SRS ( P = .0001). Rates and overall improvement were similar. CD was not associated with decreased satisfaction ( P = .28). CONCLUSION: More than 47% (47.7%) of patients without preop cervical deformity develop new postop cervical deformity after ASD surgery. Independent predictors of new onset CD at 2 years include diabetes, higher preop TS-CL, and ending instrumentation above T4. Significant improvements in HRQL scores occurred despite the development of postoperative CD.